The Implementation of Adaptive Physical Education Program for Blind Students at SMP Modern Islamic School Surakarta - Subroto, Rahmat; Hikmawati, Lusi; Lestari, Tri; Surtikanthi, Nanda Dewi; Fatmawati, Riska; Akhsanitaqwim, Yochidamai; Sugini (Indonesian Journal of Disability Studies, 2021)
In the era of the Covid-19 pandemic, the government implemented a distance learning system for students at all levels of education. This has an impact on various changes in learning methods, including for the subjects of Physical Education, Sports, and Health. The importance of learning sportsÂ during the pandemic is the right of every student, including students with special needs. In fact, children who need special services are often excluded from teaching and learning activities in physical education. So adaptive physical education is needed so that it can serve the learning needs of blindÂ students and lead students to achieve excellent health. To overcome the persistence of the above problem, the authors implemented an adaptive physical education program aimed at blind students at Junior High School Modern Islamic School (SMP MIS) Surakarta. The main program is train students to do an adaptive rhythmic gymnastics. This program consisting of Ayo Pahami (Lets Understand), Ayo Praktikkan (Lets Practice), and Ayo Lanjutkan (Lets Continue) carried out online through the WhatsApp Group. In general, this program implementation activities can run well. This is evidenced by the results of written test and also performance test. Quantitatively, the average students score is 60 while the average teachers score is 84 for the written test, and the average students score for performance test is 71,2 which is considered as skilled. Qualitatively, all students understand and can memorize the whole movements of the rhythmic gymnastics. Habituation and parental/teacher guidance is needed to boost students' ability in practicing the movements so that their motor skills can improve progressively. We also arrange ETAS organizational structure that aims to encourage students to continue their rhythmic gymnastics habits and is expected new extracurricular in the future.